Cyclic CO2 capture performance of carbide slag. Issue 4 (16th February 2016) - Zhang, Dengfeng; Li, Songgeng; Song, Wenli; Lin, Weigang
ABSTRACT: The carbonate looping process is a promising technology for CO2 capture. The decay of sorbents reactivity over multiple cycles is an obstacle for realizing the carbonate looping process. In this work, the reactivity and stability of carbide slag for CO2 capture have been examined. The results show that carbide slag exhibits superior CO2 capture performance even at severe calcination temperatures in comparison with limestones, shells, pure CaCO3, and Ca(OH)2 . X-ray diffraction analysis shows that there is mayenite (Ca12 Al14 O33 ) formed in the calcination step for carbide slag, which is the main reason for its high stability in the carbonate looping process.